Almazán Tomás, David / Barlés Báguena, Elena (coordinadores) (2019): Japón, España e Hispanoamérica: identidades y relaciones culturales. Zaragoza: Prensas de la Universidad de Zaragoza - Pano Gracia, José Luis (Mirai. Estudios Japoneses, 2020)